LINGUISTIC AMBIGUITY VERSUS VAGUENESS IN BRITISH PROVERBS - Kairytė, Arūnė; Bikelienė, Lina (Verbum, 2016)
Language, as the main communication tool, serves to deliver a desired message to the interlocutor. Discourse, however, sometimes implies multiple or imprecise meaning, i.e. it is ambiguous or vague. Many language areas and types of discourse are believed to employ the phenomena to achieve a desired effect. Indeterminacy in language could also be unintentional and happen accidentally. The present study aims at analysing the use of linguistic ambiguity and vagueness in one hundred British proverbs. Data for this research were chosen using a simple random sampling method from the Internet page ‘Learn English Today’. The findings reveal only marginal differences in the quantitative use of these linguistic devices. The study also reports on the most prevalent functions performed by ambiguity and / vagueness.